Baby - Monninger, Joseph (Asheville, N.C. : Front Street, 2007)
Fifteen-year-old Baby's last chance at foster care is with the Potters, and while she likes them and enjoys learning to race their sled dogs, she feels she should go back on the streets with her boyfriend if she cannot find the mother who has deserted her again.
Bulletin of the Center for Children's Books starre.
Young Adult
Keywords: Dogs -- Fiction; Foster home care -- Fiction; Sled dog racing -- Fiction; Sled dogs -- Fiction; Social service -- Fiction; Dogs -- Fiction; Foster home care -- Fiction; Sled dog racing -- Fiction; Sled dogs -- Fiction; Social work -- Fiction; New Hampshire -- Fiction; New Hampshire -- Fiction